Portfolio System in Teaching Writing: EFL Students' Perceptions - Tungga Pramudya Utama (Jurnal Pedagogy, 2020)
The portfolio system appears as one alternative answer for such a challenge encountered by an English teacher. The research about the portfolio system that focused on students' perception is quite necessary since it helps the teachers and students of the English language find a proper way of learning writing skills. This study aimed to investigate the students' perception of using a portfolio system to improve writing ability in teaching writing skills in English as a foreign language to high school students. The participants of this research were four students of high school. In conducting this case study, the researcher collected data from the interview. This research found that the students favored implementing a portfolio system to improve their English writing skills. This research stands as a contribution to teaching English writing skills. This study suggests that a portfolio system is a useful tool for teaching English writing skills in secondary education. It can use the teacher to facilitate the students by giving feedback on their writing to encourage their writing performance.